2011
DOI: 10.1002/pssc.201000864
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects in aluminium nitride bulk crystals visualized by cathodoluminescence maps

Abstract: Structural defects in aluminium nitride (AlN) get visible in panchromatic cathodoluminescence (CL) maps as luminescence at 340 nm and 630 nm is locally enhanced. Low‐angle grain boundaries (LAGBs) and dislocations can be detected as long as they are sufficiently decorated and the defect‐related contrast is higher than local variations in background CL intensity. We applied the method to c ‐plane and a ‐plane cuts of one of our off‐oriented grown AlN crystals and describe occurrence, routes, and dissolution int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A broad CL band at around 2.0 eV, increasing drastically at low‐angle grain boundaries (LAGBs), was found by Bickermann et al. in AlN bulk crystals with [O] and [C] concentrations of few 1018cm3. The authors attributed this band to impurities or point defects concentrated at these LAGBs.…”
Section: Discussionmentioning
confidence: 87%
“…A broad CL band at around 2.0 eV, increasing drastically at low‐angle grain boundaries (LAGBs), was found by Bickermann et al. in AlN bulk crystals with [O] and [C] concentrations of few 1018cm3. The authors attributed this band to impurities or point defects concentrated at these LAGBs.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, a higher oxygen concentration at the growth interface is supported by observations of increased cathodoluminescence (CL) intensity attributed to oxygen on N‐polar surfaces . Considering the presence of oxygen near the dislocations, previous studies have shown that point defects such as oxygen and aluminum vacancies increase the sub‐bandgap CL in the vicinity of dislocations by two orders of magnitude . Any oxygen present in the vicinity of the precipitate would rather bond to aluminum than forming tungsten oxide (due to the higher electronegativity difference between Al and O), or it would decorate the dislocation itself, in accordance with the increase of oxygen at the precipitates observed in the EPMA measurements.…”
Section: Resultsmentioning
confidence: 90%